Предмет: Математика,
автор: nanogenia
Спростіть вираз: -10 (3c - 2) - (-c-3)
Ответы
Автор ответа:
3
Ответ:-29с+23
Пошаговое объяснение:
- 10(3c - 2) - ( - c - 3) = - 30с+ 20 + c + 3 = -29с+23
Автор ответа:
3
Пошаговое объяснение:
-10(3с - 2) - (-с - 3) = -30с + 20 + с + 3 =
(-30с + с) + (20 + 3) = -29с + 23
nanogenia:
Легенда меня заметила)
Похожие вопросы
Предмет: Алгебра,
автор: clocclac712
Предмет: История,
автор: lyaysankhabibi
Предмет: Экономика,
автор: adv1142
Предмет: Литература,
автор: Edvarder
Предмет: Информатика,
автор: nern488